Myosin light chain kinase steady‐state kinetics: comparison of smooth muscle myosin II and nonmuscle myosin IIB as substrates. (16th August 2016) - Alcala, Diego B.; Haldeman, Brian D.; Brizendine, Richard K.; Krenc, Agata K.; Baker, Josh E.; Rock, Ronald S.; Cremo, Christine R.
Abstract : Myosin light chain kinase (MLCK) phosphorylates S19 of the myosin regulatory light chain (RLC), which is required to activate myosin's ATPase activity and contraction. Smooth muscles are known to display plasticity in response to factors such as inflammation, developmental stage, or stress, which lead to differential expression of nonmuscle and smooth muscle isoforms. Here, we compare steady‐state kinetics parameters for phosphorylation of different MLCK substrates: (1) nonmuscle RLC, (2) smooth muscle RLC, and heavy meromyosin subfragments of (3) nonmuscle myosin IIB, and (4) smooth muscle myosin II. We show that MLCK has a ~2‐fold higher k cat for both smooth muscle myosin II substrates compared with nonmuscle myosin IIB substrates, whereas K m values were very similar. Myosin light chain kinase has a 1.6‐fold and 1.5‐fold higher specificity ( k cat /K m ) for smooth versus nonmuscle‐free RLC and heavy meromyosin, respectively, suggesting that differences in specificity are dictated by RLC sequences. Of the 10 non‐identical RLC residues, we ruled out 7 as possible underlying causes of different MLCK kinetics. The remaining 3 residues were found to be surface exposed in the N‐terminal half of the RLC, consistent with their importance in substrate recognition. These data are consistent with prior deletion/chimera studies and significantly add to understanding of MLCK myosin interactions. Significance of the study: Phosphorylation of nonmuscle and smooth muscle myosin by myosin light chain kinase (MLCK) is required for activation of myosin's ATPase activity. In smooth muscles, nonmuscle myosin coexists with smooth muscle myosin, but the two myosins have very different chemo‐mechanical properties relating to their ability to maintain force. Differences in specificity of MLCK for different myosin isoforms had not been previously investigated. We show that the MLCK prefers smooth muscle myosin by a significant factor. These data suggest that nonmuscle myosin is phosphorylated more slowly than smooth muscle myosin during a contraction cycle.